2022
DOI: 10.1172/jci.insight.159590
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA topology depends on its subcellular and cellular origins in cancer

Abstract: S.V.B. is inventor on patents related to cell-free DNA mutation (PCT/US2014/02502) and methylation (PCT/CA2018/000141, PCT/CA2018/000203, US63/041,151) analysis technologies that are unrelated to this work and have been licensed to Roche Molecular Diagnostics and Adela, respectively. Unrelated to this work, S.V.B. is a co-founder of, has ownership in, and serves in a leadership role at Adela.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…Another possible factor in the discrepancy could have been selection of patients with high mutational burden in previous studies and large plasma volumes (up to 12 mL) used to isolate evDNA [ 15 ], which would make mutations in evDNA easier to detect. In line with our results, however, are recent studies suggesting that only a small percentage (<1%) of sEVs from patients with cancer contain DNA [ 25 ], and that DNA is rarely associated with EVs [ 26 ]. Recently, data from a seminal study also showed that exosomes, the EVs thought to carry DNA, do not contain any DNA at all [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…Another possible factor in the discrepancy could have been selection of patients with high mutational burden in previous studies and large plasma volumes (up to 12 mL) used to isolate evDNA [ 15 ], which would make mutations in evDNA easier to detect. In line with our results, however, are recent studies suggesting that only a small percentage (<1%) of sEVs from patients with cancer contain DNA [ 25 ], and that DNA is rarely associated with EVs [ 26 ]. Recently, data from a seminal study also showed that exosomes, the EVs thought to carry DNA, do not contain any DNA at all [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…This means that most of the cir-mtDNA are associated with structures whose size is over 0.22 µm. Note, our observations point to the existence of particles containing mtDNA in the circulation, as it has been previously indicated by plasma filtrates (Chiu et al, 2003;Malkin et al, 2022). In addition, our data agree with Arance-Criado's observation (Arance-Criado et al, 2020), in HI, of a 99.4% decrease of cir-mtDNA following the HS step using a protocol equivalent to the cirDNA-SPP (Supplementary Table S4A).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, when taking together fragmentomics and plasma fractionation data, we infer that a fraction, at least, of EVs contains mitochondrial full length circular DNA or mitochondria particles that could be internally or externally associated with EVs. Thus, we do not preclude the possibility that mitochondria particle free mtDNA may exist in blood circulation in association with EVs, as reported previously ( Malkin et al, 2022 ). However, its amount corresponds to a minor fraction of the total cir-mtDNA.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Mitochondrial DNA showed increases over time, indicating that the release of DNA from these organelles by the lysis buffer does not occur as quickly as the cellular genomic DNA. Moreover, a stable contribution from distinct pools of mtDNA might be important for liquid biopsy applications [ 27 29 ]. While it is possible that some contribution of non-genomic DNA may also arise from exosomes and other extracellular vesicles, due to the presence of lysis buffer the ability to delineate these sources by standard techniques is not possible [ 30 ].…”
Section: Discussionmentioning
confidence: 99%